KANDUNGAN BAKTERIOLOGIS AIR SUMUR GALI TERHADAP JARAK JAMBAN WARGA DI DUSUN REPUK MUR DESA SEPAKEK KECAMATAN PERINGGARATA KABUPATEN LOMBOK TENGAH - Dini Yuliansari (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2020)
Bacteriological water pollution is an event that still often occurs, namely the entry of microorganisms originating from human feces or animal droppings into clean water sources. The dug well is clean water facilities that are still used by the average Indonesian population with a lower middle economic level. One of the things that affects the quality of water from a dug well is the distance of the latrine. This is because the closer the water source is to the source of the pollutant, the easier the source of the pollutant seeps into the well following the flow of ground water in the center of the well. The purpose of this study was to look at the bacteriological content of dug well water based on the distance of the latrine to the dug well water source. This type of research used in this study is an experimental research that is research conducted by measuring the distance of dug wells with a toilet and measurement of bacteriological quality of dug well water. The results of the study revealed that the distance of the dug wells with latrines within 10 meters, 5 meters, 2 meters has different bacteriological content. Dug wells which are 10 meters in distance with latrines have a total number of coliforms of 350 MPN / 100 ml, dug wells that are 5 meters in distance with latrines have a number of coliforms 27 MPN / 100 ml, dug wells that are 2 meters in distance with latrines have a number of coliforms of 1600 MPN / 100 ml.